Granulomatózni orchitida - Povýsil, C (Ceskoslovenska patologie, 1980)
Granulomas consisted of mononuclear elements of different size, and fell into the following three basic categories: 1. phagocytic type of epitheloid cells with multiple tiny phagolysosomal-type dense bodies, 2. epitheloid cells without phagolysosomal apparatus, 3. macrophages with larger phagolysosome sporadically containing particles reminiscent of residua of partially "digested" bacteria. Isolated malacoplakic bodies were found in elements of this type. The findings are examined in the discussion section.
Keywords: Orchitis; orchitida; Humans; Adult; senioři; testis; granulom; mužské pohlaví; Aged; lidé; Male; Testis; Granuloma; dospělí